FUNGSI PONDOK PERSULUKAN BABUSSALAM DALAM PEMBINAAN MORAL DI BATANG KUIS KAMPUNG RUMBIA - Dahlia Lubis; Husnel Anwar; Ayu Fadillah (AL-HIKMAH:Jurnal Theosofi dan Peradaban Islam, 2020)
The function of the Pondok Pesulukan in Moral Development, aims so positively towards the community, ranging from parents, adolescents, and children with the Moral planting that is so impacting for adolescents around the Babussalam Persulukan Pondok in Batang Kuis Rumbia Village. In this study, researchers used a type of field research research with data collection techniques from Mr. Guru Sheikh Abdurrahman Harahap, murshid, as well as Community Leaders, and Village Heads in Batang Kuis Kampung Rumbia in this study with later supported literary studies related to theoretical opinions. Findings of Moral formation research results from Jama'ah: The Jama'ahs in the Babussalam Persulukan are very close to Allah by multiplying or deepening the knowledge that has been applied by Mr. Sheikh Abdurrahman Harahap conducted by researchers the condition of moral coaching activities is going pretty well, done with several methods including the habituation method, the admonition method, the exemplary method, the disciplinary method and the at-targhīb and at-tarhīb methods (rewards and punishments). This can be seen from the positive cooperation between the Teachers and Murshid and the community around the Persulukan environment. This research concludes that the pondok siluk in the thatch village can provide moral guidance through Sufism seems to be more effective than merely doctrine of moral science that is theoretical, so Sufism is expected to overcome the spiritual crisis and moral crisis both so that they become accustomed to doing in life day-to-day, both in the community, family, and at school, there is a need for habituation and exercises that are started from childhood by parents.Keywords: Cottage Towards, Moral Guidance.